Using qualitative methods to develop a contextually tailored instrument: Lessons learned - Haeok Lee; Peter Kiang; Minjin Kim; Semira Semino-Asaro; Mary Ellen Colten; Shirley S Tang; Phala Chea; Sonith Peou; Dorcas C Grigg-Saito (Asia-Pacific Journal of Oncology Nursing, 2015)
Objective: To develop a population-specific instrument to inform hepatitis B virus (HBV) and human papilloma virus (HPV) prevention education and intervention based on data and evidence obtained from the targeted population of Khmer mothers reflecting their socio-cultural and health behaviors. Methods: The principles of community-based participatory research (CBPR) guided the development of a standardized survey interview. Four stages of development and testing of the survey instrument took place in order to inform the quantitative health survey used to collect data in stage five of the project. This article reports only on Stages 1-4. Results: This process created a new quantitative measure of HBV and HPV prevention behavior based on the revised Network Episode Model and informed by the targeted population. The CBPR method facilitated the application and translation of abstract theoretical ideas of HBV and HPV prevention behavior into culturally-relevant words and expressions of Cambodian Americans (CAs). Conclusions: The design of an instrument development process that accounts for distinctive socio-cultural backgrounds of CA refugee/immigrant women provides a model for use in developing future health surveys that are intended to aid minority-serving health care professionals and researchers as well as targeted minority populations.